You don't know everything, Jilly P! - Gino, Alex (Scholastic Press, 2018)
When her new baby sister is born deaf, Jilly makes an online connection with a fellow fantasy fan, who happens to be black and deaf, and begins to learn about the many obstacles that exist in the world for people who are different from her.